PENGARUH BAURAN PEMASARAN DAN PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ONLINE DI SHOPEE (Studi Kasus Pada Gen Z di Kedusunan Kadugede Desa Sirnaputra) - Ronayah, Siti; Mufidah, Zahra Ramdhania; Abdurachman, Aditia; Ardhiansyah, Ardhiansyah; Agustian, Aldy (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
The aim of this study is to identify how much marketing and consumer behavior interact well in part and simultaneously influence the decisions made when making online purchases at the shopee on the consumer generation Z in the kadugede duo that is in the village of Sirnaputra Tasikmalaya. The method in this research is to use the quantitative method. Sampling in this study using accidental sampling. The total number of respondents to this study was 163 respondents. Data collection method used using data through a lift or a questionnaire. This analysis technique uses double linear regression analysis and descriptive analysis. The results showed that partially mixed marketing variables and consumer behavior have a positive and significant influence on online purchasing decision variables. Simultaneously, mixed marketing and consumers behaviors have a significant impact on online purchase decision variable.